Strategies for management of strongyloidiasis in migrants from Sub-Saharan Africa recently arrived in Italy: A cost-effectiveness analysis. Issue 36 (July 2020) - Zammarchi, Lorenzo; Tilli, Marta; Botta, Annarita; Buonfrate, Dora; Bartoloni, Alessandro; Boccalini, Sara
Abstract: Background: The Italian and the European Centre for Disease Control and Prevention guidelines both recommend a systematic serological screening for strongyloidiasis in sub-Saharan migrants (SSA), however, studies on clinical and economic impact of this strategy in the Italian and European settings are lacking. Methods: A population of 100, 000 migrants from SSA to Italy was considered and a Markov decision tree model was developed to assess the clinical and economic impact of two interventions for strongyloidiasis compared with the current practice (passive diagnosis of symptomatic cases): a) universal serological screening and treatment with ivermectin in case of positive test b) universal presumptive treatment with ivermectin. One and 10-year time horizon in the health-care perspective were considered. Results: In the one and 10-year time horizon respectively the costs for passive diagnosis was €1, 164, 169 and €9, 735, 908, those for screening option was € 2, 856, 011 and € 4, 959, 638 and those for presumptive treatment was €3, 538, 474 and € 4, 883, 272. Considering the cost per cured subject in the one-year time horizon, screening appears more favorable (€209.53), than the other two options (€232.55 per presumptive treatment and €10, 197.29 per current strategy). Incremental cost-effectiveness ratio (ICERs) of screening strategy and presumptive treatment were respectively 265.27 and 333.19. The sensitivity analysis identified strongyloidiasis' prevalence as the main driver of ICER. Conclusions: Compared to the current practice (passive diagnosis) both screening and presumptive treatment strategies are more favorable from a cost-effectiveness point of view, with a slight advantage of the screening strategy in a one-year time horizon.